Implementing E-Portfolio in Self-Monitoring Phase of Self-Regulated Learning Strategy in Writing Course: A Case Study - Nurjanah, Ratih Laily; Waluyo, Sri (Universitas Negeri Semarang, 2024)
This study proposes a model of self-monitoring phase of Self-Regulated Learning using E-Portfolio in writing an essay. The method used was case study which aims to take an activity or phenomenon as an example. The E-Portfolio tool used was Wordpress.com. The proposed model covers ten stages begin with students making the E-Portfolio, stating their goals, taking notes exploring materials, taking notes on feedback given by the lecturer and peers, reviewing the feedback, performing self-evaluation, presenting the results of evaluation, discussing with peers about their difficulties, and asking and discussing with the lecturer about personal difficulties found during the process. To achieve the desired result from implementing E-Portfolio in Self-Monitoring phase of SRL, teacher/lecturer should consider several factors among others learning objective, participants, tool used, the outcome expected, and not to mention infrastructure available. Several challenges in implementing this strategy include the infrastructure such as internet connection and the hardware supports. In addition, students’ reluctancy to do the self-reflection phase due to self-distrust with their capability and skill or their skepticism towards the teacher/lecturer should be overcome with adequate guidance and frequent encouragement for the success of this strategy.